Survey on knowledge of non-alcoholic fatty liver disease (NAFLD) among doctors in Sri Lanka: a multicenter study - Anne Thushara Matthias; Anthony Nilesh Ranjeev Fernandopulle; Suranjith L. Seneviratne (BMC Research Notes, 2018)
Abstract Objectives There has been a global increase in the incidence and prevalence of NAFLD. We assessed the knowledge and awareness of NAFLD among gastroenterology doctors in three state sector hospitals. Results 80 medical officers and 58 post-graduate trainee doctors/consultants responded. 110 (79.7%) considered NAFLD a major health problem whilst 97 (70.3%) thought the prevalence of NAFLD was 10–40%. 52.9% saw 12–24 patients with NAFLD/year. A vast majority knew the risk factors for NAFLD: 127 (92.7%) diabetes mellitus, 135 (97.8%) Obesity, 132 (95.7%) Dyslipidemia and 87 (63%) PCOS. The methods for diagnosis were recognized by: USS 132 (95.7%), MRI 34 (24.6%), transient elastography 23 (16.7%) and liver biopsy 88 (63.8%) while, 53 (38.4%) recognized the non-invasive methods available for diagnosis. The trends in referral were lower than expected: 85 (61.6%) refer to a Gastroenterologist/Physician, 53 (38.4%) to a Gym, 67 (48.6%) to a weight loss clinic and 45 (32.6%) to a dietician. Significantly more postgraduate trainee doctors: recognized the availability of non-invasive investigations for NAFLD (P = 0.01) and read guidelines on NAFLD (P = 0.02) compared to non-trainee doctors. As a whole, a majority (57.2%) had not attended a lecture or read a guideline on NAFLD. The barriers for management included: lack of confidence 70 (50.7%) and time constraints 58 (42%).